The knowledge of school managers using key elements of an HIV and AIDS workplace policy at Shatale circuit in the Mpumalanga Province - Tjale, Nkgatla Michael Ludwick (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2012